Identification With All Humanity Predicts Prosocial and Political Action Intentions During COVID-19 - Lantos, Nóra Anna; Engyel, Márton; Hadarics, Márton; Nyúl, Boglárka; Csaba, Sára; Kende, Anna (Frontiers in Political Science, 2022)
In case of a global crisis, such as the COVID-19 pandemic, inclusive identities are essential for coordinated action and for pro-social behaviour on behalf of vulnerable groups. We tested how identification with all humanity versus the national ingroup play a role in supporting vulnerable groups by prosocial action on one hand, and on the other hand, how these factors mobilize people to be willing to put pressure on authorities for the interest of their communities. We hypothesized that identification with all humanity (compared to national identity) leads to empathy for vulnerable groups and prosocial action intention on behalf of them to a higher degree, and unlike national identity, it also predicts political action intention. Data was collected with an online survey at four timepoints in Hungary. Our path analyses showed that both human and national identity predicted empathy and prosocial action intentions toward groups in need. Human identification was a positive, and national identification a negative predictor of political action intention. While both identification with all humanity and national identity united people in caring for others in a crisis, the two forms of identification divided them in questioning governmental measures. Identification with all humanity made people not only sensitive to vulnerable groups, but critical to the government and made them more willing to challenge political decisions. Identification with all humanity became a predictor of political action intention, showing that solidarity could manifest both in prosocial and political action tendency in the context of COVID-19.